In-session seizures during low-frequency repetitive transcranial magnetic stimulation in patients with epilepsy - Rotenberg, Alexander (2009)
Low-frequency repetitive transcranial magnetic stimulation (rTMS) is emerging as a therapeutic tool for patients with intractable epilepsy. Although seizures during treatment have been reported as adverse events in some patients, the nature and severity of seizures that may be provoked by low-frequency rTMS in patients with epilepsy have not been extensively studied. Accordingly, this article documents seizures in patients (n = 5) with intractable epilepsy and average seizure frequency greater than one per day who underwent 1-Hz rTMS for seizure suppression. We report three observations in the present case series: (1) in each instance the in-session seizure was typical in semiology to the patient’s habitual seizures, (2) the duration of each documented seizure was either the same as or shorter than the patients’ baseline seizures, and (3) the overall neurological outcome on follow-up was not affected by the in-session seizures. More data will be required for valid conclusions with respect to safety and tolerability of low-frequency rTMS in patients with epilepsy, but it is noteworthy from our perspective that seizures during rTMS in this series were similar to the patients’ habitual seizures, occurred in patients with epilepsy with baseline seizure frequency exceeding one per day, and did not correlate with a poor neurological outcome or with absence of clinical response to rTMS.